E-Government Development Under the Decentralization Reform in Ukraine: The Experience of Poland and Slovakia - Vasyl MARCHUK (Communications of International Proceedings, 2021)
The aim of the study was to evaluate the features of the introduction of e-government in Poland, Slovakia and Ukraine. The scope of analysis covered national features of introduction of system of electronic public services. The study is aimed to show the differences of the implementation of e-government in EU and non-EU countries. In Ukraine, the development of the e-government system coincided with a long-therm decentralization reform, which introduced a new administrative-territorial system to strengthen the capacity of local governments. For Ukraine, the experience of Poland and Slovak Respublic is important in terms of introducing affordable services for the population and improving living standards as well as meet the requirements of the Association Agreement with EU and fulfill international obligations.
Keywords: E-Government; Decentralization; United Territorial Community; Public Authotities; State Service.